Future Literacies through Digital Narratives: Preparing Students for the Storytelling Society of Tomorrow - Ida Bagus Purwa Sidemen; Ni Nyoman Wahyu Adi Gotama; Ida Ayu Putu Sari; Irene Rosalina; Sokha Dara (International Journal of Educational Narratives, 2025)
Background. The rapid evolution of digital communication has transformed storytelling into a foundational literacy of the 21st century, redefining how students create, interpret, and share meaning. Purpose. This study explores the role of digital narratives in cultivating “future literacies,” emphasizing creativity, critical thinking, collaboration, and digital ethics as essential competencies for the storytelling society of tomorrow.   Method. The research aims to identify how digital storytelling can be integrated into formal education to prepare learners for a future dominated by narrative-driven communication across media platforms. Results. The findings demonstrate that digital storytelling fosters multiliteracies visual, media, and technological while strengthening students’ reflective and ethical awareness in digital environments. Participants exhibited enhanced capacity to structure arguments, convey empathy, and critically evaluate digital content.   Conclusion. The study concludes that digital narratives are not merely tools for creative expression but frameworks for developing adaptive literacy practices aligned with global digital transformation. Integrating digital storytelling into education equips learners to become responsible and innovative communicators in a networked world.